RSAD2 and AIM2 modulateCV-A16 and EV-A71 replication in neuronal cells in different ways that may be associated with their 5′ non-translated regions - David, Perera (American Society for Microbiology, 2017)
Coxsackievirus A16 (CV-A16) and Enterovirus A71 (EV-A71) are closely related enteroviruses that cause the same hand, foot and mouth disease but neurological complications occur only very rarely in CV-A16 compared to EV-A71 infections. To elucidate host responses that may be able to explain these differences, we performed transcriptomic analysis and qRT-PCR in CV-A16 infected neuroblastoma cells (SK-N-SH) which showed that the radical s-adenosyl methionine domain containing 2 (RSAD2) was the highest up-regulated gene in the anti-microbial pathway. Increased RSAD2 expression was correlated with reduced viral replication while RSAD2 knockdown cells were correlated with increased replication. EV-A71 replication showed no apparent correlation to RSAD2 expressions. Absent in melanoma 2 (AIM2) which is associated with pyroptosis cell death was upregulated in EV-A71 infected neurons but not in CV-A16 infection, suggesting that the AIM2 inflammasome played a significant role in suppressing EV-A71 replication. Chimeric viruses derived from CV-A16 and EV-A71 but containing swapped 5′ non-translated regions (5′ NTR) showed that RSAD2 expression/viral replication and AIM2 expression/viral replication patterns may be linked to the 5′ NTRs of parental viruses. Differences in secondary structure of internal ribosomal entry sites within the 5′ NTR may be responsible for these findings. Overall, our results suggest that CV-A16 and EV-A71 elicit different host responses to infection, which may help explain the apparent lower incidence of CV-A16 associated neurovirulence in HFMD outbreaks compared to EV-A71 infection.